Criminology explains human trafficking - Williamson, Sarah Hupp (Criminology explains, 2024)
"This book will provide a comprehensive and accessible overview of criminological theory as it applies to the topic of human trafficking. This book uses real-life applications and case studies to highlight the links between theory, research, and policy. This includes applying a diverse range of criminological theory to understand different forms of trafficking, victims versus offenders, the role of migration and globalization, domestic and international law, anti-trafficking efforts, and more. Through the use of discussion questions, activities, and policy boxes, readers will gain a deeper understanding of theory as it applies to the field of human trafficking, including how various levels of analysis from the local to the global are often linked"--